Auditing Clinical Outcomes after Introducing Off-Licence Prescribing of Atypical Antipsychotic Melperone for Patients with Treatment Refractory Schizophrenia - Frank Röhricht; Seema Gadhia; Rinku Alam; Melissa Willis (The Scientific World Journal)
Aims and Method. To evaluate the practical utility of off-licence prescribing and clinical outcomes of treatment with atypical antipsychotic Melperone. Method: Prospective data collection on patient’s clinical characteristics and outcomes. Results. 17 patients with a diagnosis of refractory schizophrenia were identified as suitable for off-license prescribing of Melperone and commenced treatment (13 were previously treated with Clozapine). Seven of those currently remain on Melperone (41%), and for six patents, the BPRS symptom scores reduced significantly over time (24–61%) additionally patients displayed improvements of their quality of life. Six patients were discontinued due to noncompliance and/or side effects. Melperone was ineffective in the other four patients. Clinical Implications. The example of a small group of patients responding well to a comparably safe and inexpensive atypical antipsychotic with favourable side effect profile should encourage clinicians to use this tool as third-line treatment and to conduct more systematic clinical research.